Firms' investment decisions in response to demand and price uncertainty - Catherine Fuss; Philip Vermeulen (European Central Bank (ECB), 2004)
We estimate the effect of demand and price uncertainty on firms' investment decisions from a panel of manufacturing firms. Uncertainty measures are derived from firms' subjective qualitative expectations. They are close to their theoretical counterparts, the variances of future demand and price shocks. We find that demand uncertainty depresses planned and realized investment, while price uncertainty is insignificant. This is consistent with the behavior of monopolistic firms with irreversible capital (Caballero, 1991). Further, firms revise their investment plans very little. They may do so in response to new information on sales growth, but not as a result of reduced uncertainty.
Keywords: D21; D24; D81; D92; C23; 330; Investment; panel data; real options; survey data; uncertainty